2007
DOI: 10.1098/rspb.2007.0337
|View full text |Cite
|
Sign up to set email alerts
|

Drd4 gene polymorphisms are associated with personality variation in a passerine bird

Abstract: Polymorphisms in several neurotransmitter-associated genes have been associated with variation in human personality traits. Among the more promising of such associations is that between the human dopamine receptor D4 gene (Drd4) variants and novelty-seeking behaviour. However, genetic epistasis, genotypeenvironment interactions and confounding environmental factors all act to obscure genotype-personality relationships. Such problems can be addressed by measuring personality under standardized conditions and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
243
4
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(261 citation statements)
references
References 31 publications
(82 reference statements)
13
243
4
1
Order By: Relevance
“…The four key questions on the causation, ontogeny, adaptivity, and phylogeny that Tinbergen (1963) originally formulated to study behavior at the species level are increasingly refined to the individual level. Animal researchers study genetic variation (Fidler, van Oers, Drent, Kuhn, Mueller, & Kempenaers, 2007), epigenetic influences , psychobiological parameters (Kinnally, Lyons, Abel, Mendoza, & Capitanio, 2008;Schneider & Suomi, 1992), and developmental conditions (Fairbanks & McGuire, 1993) associated with behavioral differences among individuals. Assuming that "nothing in biology makes sense except in the light of evolution" (Dobzhansky, 1973), sophisticated models are developed to explain their emergence from evolutionary viewpoints (Dall, Houston, & McNamara, 2004;Wolf, van Doorn, Leimar, & Weissing, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The four key questions on the causation, ontogeny, adaptivity, and phylogeny that Tinbergen (1963) originally formulated to study behavior at the species level are increasingly refined to the individual level. Animal researchers study genetic variation (Fidler, van Oers, Drent, Kuhn, Mueller, & Kempenaers, 2007), epigenetic influences , psychobiological parameters (Kinnally, Lyons, Abel, Mendoza, & Capitanio, 2008;Schneider & Suomi, 1992), and developmental conditions (Fairbanks & McGuire, 1993) associated with behavioral differences among individuals. Assuming that "nothing in biology makes sense except in the light of evolution" (Dobzhansky, 1973), sophisticated models are developed to explain their emergence from evolutionary viewpoints (Dall, Houston, & McNamara, 2004;Wolf, van Doorn, Leimar, & Weissing, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The dopamine receptor D4 gene (DRD4) is involved in curiosity behaviour and novelty seeking in different mammals such as mice (Rubinstein et al, 1997), dogs (Niimi et al, 1999), horses (Momozawa et al, 2005) and birds (Fidler et al, 2007). In humans, DRD4 is also associated with novelty seeking, an aspect of human temperament (Keltikangas-Jarvinen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, genetic variation in a candidate gene, the D4 dopamine receptor, DRD4, has been related to consistent individual differences in exploratory behaviour in a wild bird, the great tit (Fidler et al 2007), selected lines of a domesticated bird, laying hens (Flisikowski et al 2009), horses (Momozawa et al 2005) and humans (Munafo et al 2008), suggesting that exploratory behaviour in this diverse array of vertebrate species shares a common molecular basis (but see Korsten et al 2010). It is important to stress that in these cases, a polymorphism has been found in this receptor, but the functional significance of this polymorphism has not been tested in all species.…”
Section: What Can Whole Genome Data Tell Us About the Extent Of Similmentioning
confidence: 99%
“…Although traditional quantitative genetic approaches have helped us to understand the genetic architecture underlying natural variation in personality traits (Dingemanse et al 2002;Drent et al 2003;RĂ©ale & Festa-Bianchet 2003;Bell 2005;Dochtermann & Roff 2010), such approaches necessarily measure phenotypes, rather than the genes that underlie behavioural variation, and therefore have limited use for understanding specific molecular and genetic mechanisms. When studies have tried to relate specific individual genes to personality traits in humans, model laboratory animals or domesticated animals (Champoux et al 2002;Geller et al 2002;Adamec et al 2006;Fidler et al 2007), they have found that specific candidate genes, such as the dopamine receptor 4 (DRD4), the serotonin transporter (SERT) and monoamine oxidase (MAO), only explain a small fraction of the total genetic variation (reviewed in Reif & Lesch 2003), indicating that we are yet to learn the identity of most of the important genes (or that all of the genes are of very small effect). Moreover, epistatic interactions between loci make it difficult to study the effects of single genes one-at-a-time (Mackay 2009).…”
Section: Introductionmentioning
confidence: 99%